Pembinaan Keamanan Pangan Industri Rumah Tangga Pangan (IRTP) Guna Percepatan Mendapatkan Izin Edar Di Wilayah Kota Bengkulu Tahun 2022: Pembinaan Keamanan Pangan Industri Rumah Tangga Pangan (IRTP) Guna Percepatan Mendapatkan Izin Edar Di Wilayah Kota Bengkulu Tahun 2022 - pravita sari, ayu (Poltekkes Kemenkes Bengkulu, 2023)
Food Home Industry, hereinafter abbreviated as IRTP, is a food industry that has a place of business in a residence with manual to semi-automatic food processing equipment. Food Home Industry (IRTP) can produce the resulting processed food. IRTP Production Food is processed food produced by IRTP distributed in retail packaging and labeled. For product marketing, IRTP must have a Certificate of Home Industry Food Production (SPP-IRT). There are 20 IRTPs that do not yet have certificates. This certificate will be issued by the Health Service and obtained after the IRTP owner has received training on food safety. This community service activity will facilitate Food safety training. With this community service activity, all 20 participants of IRTP owners have a Household Industry Food Production Certificate (SPP-IRT). The results showed that there was a significant increase in knowledge before and after training.